До питання інформаційного забезпечення транскордонної мобільності працівників у Європейському Союзі - Федонюк, С. В.; Fedoniuk, S. V. (Східноєвропейський національний університет імені Лесі Українки, 2013)
Discussed the problems of cross-border mobility of workers in the European Union. The proposals to improve the opportunities for cross-border mobility in terms of information provision.
To the Question of Information Providing of Cross-Border Mobility of Workers in the European Union
С. В. Федонюк, к. геогр. наук. доц., декан факультету міжнародних відносин Східноєвропейського національного університету імені Лесі Українки (Україна, м.Луцьк)
Keywords: cross-border mobility of workers; European Union; information providing